Meat tastes good, legumes are healthy and meat substitutes are still strange - The practice of protein consumption among Swedish consumers. (1st July 2022) - Röös, Elin; de Groote, Annica; Stephan, Andreas
Abstract: Replacing some meat with grain legumes would benefit human health, the environment and agriculture. This study analysed legume and meat consumption practices by investigating consumer perceptions and competences relating to lightly processed grain legumes (LPL), legume-based meat substitutes (LBMS) and meat in Sweden, and how these (and demographic variables) influenced stated intention to change consumption. Major differences in consumer perceptions of LPL and LBMS compared with meat related to product attractiveness and status, with meat seen as more fun, popular, suitable in diets and for festive occasions, and tastier. Most consumers knew of the environmental impact of meat and health benefits of LPL. Country of origin, i.e. Swedish origin, was important for many consumers (especially for meat and women). Preferences relating to health and environmental impact were important for intention to decrease meat consumption. Perceived environmental impact was important for intention to change consumption of LPL, but taste, healthiness, weight control, ease of preparation and suitability in the diet were equally or more important. Leveraging stated consumer willingness and intention to eat more LPL by making LPL more accessible to consumers could increase their consumption. For LBMS, there are still important barriers in terms of taste, familiarity and overall attractiveness of these products that need to be overcome to increase their consumption in Sweden.